2014
DOI: 10.1007/s10534-014-9717-8
|View full text |Cite
|
Sign up to set email alerts
|

Iron toxicity mediated by oxidative stress enhances tissue damage in an animal model of diabetes

Abstract: Although iron is a first-line pro-oxidant that modulates clinical manifestations of various systemic diseases, including diabetes, the individual tissue damage generated by active oxidant insults has not been demonstrated in current animal models of diabetes. We tested the hypothesis that oxidative stress is involved in the severity of the tissues injury when iron supplementation is administered in a model of type 1 diabetes. Streptozotocin (Stz)-induced diabetic and non-diabetic Fischer rats were maintained w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 35 publications
1
37
1
Order By: Relevance
“…According to the literature, increased oxidative stress leads to the release of proinflammatory cytokines, leading to further tissue damage. [22][23][24] Methotrexate is used for the treatment of pancreatic cancer, but has been shown to destroy the beta cells of the pancreas, primarily through oxidative stress. 1,2,5,24 In support of the data in the literature, we determined that in our study the number of insulin and somatostatin-positive cells significantly decreased in Group 2, when compared to that in Group 1 (Fig.…”
Section: A B Cmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the literature, increased oxidative stress leads to the release of proinflammatory cytokines, leading to further tissue damage. [22][23][24] Methotrexate is used for the treatment of pancreatic cancer, but has been shown to destroy the beta cells of the pancreas, primarily through oxidative stress. 1,2,5,24 In support of the data in the literature, we determined that in our study the number of insulin and somatostatin-positive cells significantly decreased in Group 2, when compared to that in Group 1 (Fig.…”
Section: A B Cmentioning
confidence: 99%
“…5,24 It has also been reported that ROS play a key role in decreasing immune system defense. 5,24,25 In addition, intense proinflammatory cytokine release, due to excessive ROS formation, has been reported during MTX treatment for cancer and autoimmune diseases.…”
Section: A B Cmentioning
confidence: 99%
See 2 more Smart Citations
“…This importance is observed at all levels of the tree of life. However, in humans, iron concentration higher than normal levels could become toxic by increasing oxidative stress, eventually translating to myocardial malfunction and inflammation responses to the pancreas (1). Other studies have suggested damages to adipose tissue and liver in obese persons (2).…”
Section: Introductionmentioning
confidence: 99%